2012
DOI: 10.1186/bcr3369
|View full text |Cite
|
Sign up to set email alerts
|

The risk of contralateral breast cancer in patients from BRCA1/2 negative high risk families as compared to patients from BRCA1 or BRCA2 positive families: a retrospective cohort study

Abstract: IntroductionWhile it has been reported that the risk of contralateral breast cancer in patients from BRCA1 or BRCA2 positive families is elevated, little is known about contralateral breast cancer risk in patients from high risk families that tested negative for BRCA1/2 mutations.MethodsA retrospective, multicenter cohort study was performed from 1996 to 2011 and comprised 6,235 women with unilateral breast cancer from 6,230 high risk families that had tested positive for BRCA1 (n = 1,154) or BRCA2 (n = 575) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 26 publications
7
69
1
6
Order By: Relevance
“…eCLAUS and BOADICEA make the simplifying assumption that the first and the second breast cancer are independently conditioned on BRCA1/2 genotypes. However, evidence of a strong dependency of first and second breast cancer has recently been provided [28,40,65]. Thus, these risk prediction models are currently not suitable for CBC prediction and should not be used for this purpose until they have been adjusted and validated.…”
Section: Breast Cancer Risk Prediction Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…eCLAUS and BOADICEA make the simplifying assumption that the first and the second breast cancer are independently conditioned on BRCA1/2 genotypes. However, evidence of a strong dependency of first and second breast cancer has recently been provided [28,40,65]. Thus, these risk prediction models are currently not suitable for CBC prediction and should not be used for this purpose until they have been adjusted and validated.…”
Section: Breast Cancer Risk Prediction Modelsmentioning
confidence: 99%
“…The 10-year risks were even higher with 27% and 19% for BRCA1 and BRCA2 mutation carriers, respectively (table 1). Moreover, a retrospective data analysis of the German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC) has shown that younger age at first breast cancer was associated with a higher risk of CBC [28,40]. …”
Section: Cancer Risks Of Brca1/2 Mutation Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Before performing bilateral mastectomy, it is advisable to exclude metastasis. Rhiem et al [14] have published tables relating to the probability of contracting the disease contralaterally, depending on the age at first onset and the time lag. These can be used by both physician and patient to assess the risk of contracting contralateral disease within the next 5 or 10 years.…”
Section: Secondary Prevention Of Breast Cancermentioning
confidence: 99%
“…A study by the GC-HBOC [25 ]provided data that was able to influence the decision-making process of women with unilateral breast cancer. The retrospective, multicenter cohort study was performed from 1996 to 2011 and comprised 6,235 women with unilateral breast cancer from 6,230 high-risk families that had either tested positive for BRCA1 (n = 1,154) or BRCA2 (n = 575) mutations or tested negative (n = 4,501).…”
Section: Risk-reducing Options For Brca1/2 Mutation Carriersmentioning
confidence: 99%